Systematic review of suicide prevention studies with data on youth and young adults living in low-income and middle-income countries. Issue 9 (6th September 2022) - Doty, Benjamin; Bass, Judith; Ryan, Taylor; Zhang, Allen; Wilcox, Holly
Abstract : Objectives: This review aimed to provide a summary of peer-reviewed, published literature on suicide preventive interventions with data on youth and young adults in low-income and middle-income countries (LMIC). Design: A systematic review was conducted using electronic databases of PubMed/MEDLINE, The Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Education Resources Information Center and The Campbell Collaboration databases for English-language articles published between 1 January 1990 and 15 February 2022. Eligibility criteria: Interventions of interest could include behavioural, community, clinical/medical or policy studies, or any combination of these, so long as the studies had at least one outcome of interest and at least one control group or control period. Outcomes included suicide ideation, suicide attempt and suicide. Interventions must have been conducted in an LMIC. Studies with individuals ages 0–25 in the sample were included. Articles describing data on individuals over age 25 could be included if individuals ages 0–25 were part of the sample. Results: A total of 44 eligible studies were identified, representing a broad range of universal, selective and indicated interventions. Most studies assessed interventions designed to address lethal means or mental health. Most studies were conducted in lower-middle-income or upper-middle-income countries, with the largest proportion in Asia. Assessment of outcomes across studies was heterogeneous and there were few large-scale investigations tailored specifically for youth. Conclusions: Most of the published, peer-reviewed suicide intervention research from LMIC is concentrated in a few countries. While geographical coverage to date has been limited, strategies and samples in included studies were diverse, representing populations in clinical, educational and community settings. While current findings hold promise, this review identified a need for large-scale studies designed specifically for youth.